Native Trees Provide More Benefits Than Exotic Trees When Ecosystem Services Are Weighted in Santiago, Chile - Castro-Morales, S (Springer Science and Business Media Deutschland GmbH, 2021)
Urban forests are conformed by a variable representation of native and exotic species. Because these species differ in the morpho-functional traits that possess, they may have a differential participation in the provision of ecosystem services in cities. Here, we compare ecosystem services inferred from morpho-functional traits of native and exotic tree species present in Santiago, Chile. Five traits associated with ecosystem services valuation (Vi) were scored (1 versus 0), and compared between native and exotic tree species, weighting those ecosystem services according to multi-criteria decision analysis procedure (MCDA). We found that native and exotic species did not have significant differences in the ecosystem services provided to urban dwellers (F = 1.2; P > 0.05); but these results were obtained when ecosystem services were not weighted according to their demand in Santiago. When weights were pondered, native species provided more ecosystem services than did exotic trees (F = 7.1; P < 0.008). Complementarily, we also found that the ecosystem services ranked for native and exotic species did not correlate with their spatial distribution (occupancy, Oi). These results highlight the need to use criteria based on ecosystem services to tree planting in Santiago, prioritizing native species because, in comparison to exotic ones, they provide more ecosystem services demanded city dwellers. © 2021, The Author(s).
Keywords: Alien tree; Ecosystem service; Morpho-functional trait; Tree appraisal; Urban tree